Social interaction and L2 classroom discourse - Sert, Olcay (Studies in social interaction., 2015)
"This book offers a close investigation of interactional practices in L2 classrooms, and provides a deeper appreciation of the processes involved in the co-construction of understanding and knowledge in settings for instructed language learning. Using Conversation Analysis, and referring to epistemic, multimodal, and multilingual resources, Olcay Sert interprets key interactional and pedagogical practices observed in language classrooms by closely examining the verbal and nonverbal features of teacher-student interaction; for example, gaze, gestures and orientations to classroom artefacts. With an emphasis on the multimodal and multilingual resources, this is one of the first studies to comprehensively address these issues in L2 classrooms with a clear theoretical and practical underpinning, and is an essential study for researchers and postgraduate students in TESOL and Applied Linguistics"--